Copper oxide nanoparticle impurities are responsible for the electroanalytical detection of glucose seen using multiwalled carbon nanotubes - Batchelor-McAuley, C; Wildgoose, G; Compton, R; Shao, L; Green, M (2008)
In this report we demonstrate the second known example whereby multiwalled carbon nanotubes made by the chemical vapour deposition method (cvd-MWCNTs) contain copper oxide nanoparticles within them which are responsible for the analytical signal observed, in this example the electrochemical detection of glucose. Comparisons with copper(II) oxide particles immobilised onto a basal-plane pyrolytic graphite electrode produce almost identical voltammetric responses as the cvd-MWCNTs. Similar experiments performed using an edge-plane pyrolytic graphite electrode and with an ultra-pure sample of arc-MWCNTs (made using the electric arc discharge method and free from any residual metal nanoparticle catalysts) demonstrates that these electrode substrates are inactive towards even high concentrations of glucose. Thus the edge-plane-like defects present at the termini of the graphite sheets or the ends of the MWCNTs are not, as is usually the case, the electroactive sites towards this particular analyte. It is the copper impurities which are the electroactive species responsible and MWCNTs should not be considered as suitable substrates for the electrochemical detection of glucose contrary to numerous previous claims except in so far as they provide an elegant, if adventitious, method for "wiring" copper oxide nanoparticles. © 2008 Elsevier B.V. All rights reserved.